Teachers’ Perception Towards Integration of Artificial Intelligence Tutoring-Based System in the School Curriculum: A Survey - Vivian M. Olaseni (E-Journal of Humanities, Arts and Social Sciences)
Artificial Intelligence (AI) is the theory and development of computer systems capable of performing tasks normally requiring human intelligence, such as visual perception, speech recognition, decision-making, and translation between languages. This approach has been adopted by many organizations, including schools, to facilitate the teaching and learning process. This development has raised varying opinions on the future of employment within all sectors, including the educational sector. The purpose of this research was to evaluate the perception of teachers toward the integration of AI tutoring-based systems into the school curriculum. A descriptive analysis of the quantitative design was used, and 320 teachers were purposely sampled from public secondary schools in Southwest, Nigeria. The data were collected using a questionnaire and analyzed using SPSS. The findings of the study revealed that although teachers in public secondary schools in the southwest of Nigeria are aware of the positive impact of AI tutoring, 77% of the participants have a negative disposition towards the integration of an AI tutoring-based system into the school curriculum. The factors responsible for this high level of negative disposition include age, low level of education, fear of replacement and professional specialties of the teachers. Based on these findings, it was therefore recommended that teachers be sensitized on the importance of AI tutoring and that stakeholders should propagate the message of how it would promote the standard of education in the state. The study also recommended that educational policymakers integrate the use of artificial intelligence into the school curriculum by allocating the required resources to schools and organizing staff training on the use of AI without neglecting a befitting remuneration.